On conjugate pseudo-harmonic functions - Polulyakh, Ye. (Інститут математики НАН України, 2009)
We prove the following theorem. Let U be a pseudo-harmonic function on a surface M². For a real valued continuous function V : M² → R to be a conjugate pseudo-harmonic function of U on M² it is necessary and sufficient that V is open on level sets of U.